SMS GATEWAY PADA WEBSITE GEREJA MASEHI ADVENT HARI KETUJUH (GMAHK) PALANGKA RAYA BERBASIS WEB 2.0 - Christina, Sherly; Pranatawijaya, Viktor Handrianus; Widyasari, Yolantya (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Seventh-day Adventist Church (SDA) is a branch of evangelical Christian denominations thatexist throughout the world and also in the city of Palangkaraya. Seventh-day Adventist Church (SDA)Palangkaraya need a media that can share information for the church and the media to provideinformation to the public who want to know about this church and its activities.This study methodology is the UML-based Web Engineering (UWE) that include four phases: UseCase Model, Content Model, Navigation models and Presentation models. This website is designed usingweb programming language PHP, database MySQL, Adobe Dreamweaver CS5, Javascript, Ajax, Jquery,Gammu for SMS Gateway and tested by Blackbox Testing method.The testing phase shows that the website can be used as a media to inform , promote and share theSeventh-day Adventists profiles, church activities in the image/picture, data download and the collectionof relevant links. This media could play a role in the ministry, preaching the gospel, and to be a blessingfor everyone